Financial Development and Economic Growth: An Instrumental Variables Approach - Nonga, Fidoline Ngo; Blanche, Ngo Yonga Debora; Arnaud, Ekani Evrad (Asian Journal of Empirical Research, 2022)
The objective of this article is to evaluate the effect of financial development on economic growth in the six countries of the Economic and Monetary Community of Central African States (EMCCAS) sub-region, during the period 2000-2020. To achieve our objective, we used the method of instrumental variables which are robust to autocorrelation, heteroscedasticity of errors and a possible problem of endogeneity. In addition, we used the Three Stages Least Squares method to test the robustness of our results. The results of the estimates revealed that there is an inverse relationship between financial intermediation and economic growth on the one hand and on the other hand, that there is a non-linear U-shaped relationship between the two variables. Therefore, the governments of the countries of the EMCCAS zone must implement policies aimed at supporting the guarantees of SMEs (small and medium-sized enterprises) in their credit granting processes with banks or financial institutions.